Dari Teosofi Ke Libidosofi : Dinamika Wayang Wong Tejakula, Kabupaten Buleleng, Bali, Pada Masa Orde Baru, Dan Potensinya Sebagai Penguatan Profil Pelajar Pancasila di SMA - Sitinjak, Dion Helby Sisco Sitinjak; Purnawati, Desak Made Oka Purnawati; Martayana, I Putu Hendra Mas Martayana (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
This study aims to find out the dynamics of Wayang Wong in Tejakula Village, Tejakula District, Buleleng Regency during the New Order era and the shift in values ​​of Wayang Wong Tejakula, Tejakula District, Buleleng Regency during the New Order era and its use as a strengthening of the Pancasila Student Profile in high school. The author uses a historical qualitative research method consisting of four stages, namely heuristics, source criticism, interpretation, and historiography. The results of the study show that the dynamics of Wayang Wong Tejakula cannot be separated from the modernization in the form of tourism that occurred in Bali in 1966. This can be seen from Wayang Wong Tejakula in the 1950s which was still sacred but in the 1966 era it had changed its function to become a profane art. There are several uses of Wayang Wong Tejakula media that can be used as a Pancasila Student Profile Strengthening Project in high school. The dynamics of Wayang Wong Tejakula can be used as a Pancasila Student Profile Strengthening Project in phase F (grade 11) in three learning stages, namely the introduction stage, the contextualization stage, and the action stage. Keywords: Wayang Wong Tejakula, Pancasila Student Profile, Values, New Order